116 The long-term impact of a practice-oriented research training program for clinical and translational research staff and clinicians: Evaluating workforce development outcomes over time and professional careers. - Elias Samuels; Elias Samuels; Ellen Champagne; Phillip Ianni; Claire Z. Kalpakjian; Susan L. Murphy (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: There are few training programs for health research staff and clinicians like The Practice-Oriented Research Training program, that include opportunities to conduct funded clinical and translational research. The goal of this study is to evaluate the long-term impact of this program on participants professional development and advancement. METHODS/STUDY POPULATION: The Practice-Oriented Research Training program for health research staff and clinicians was operated by the Michigan Institute for Clinical and Health Research from 2008 through 2018. Participants received training and formed teams that received financial support to conduct a clinical or translational study with a faculty mentor. Eleven cohorts comprising 111 individuals participated. The long-term impact of the program was evaluated using sequential mixed methods. All participants were invited to evaluate the program via an online survey in 2021. Respondents were invited to participate in interviews in 2022. Secondary records of the participants’ publications, grants, and professional advancement were collected. RESULTS/ANTICIPATED RESULTS: 68 participants in the PORT program published 345 papers in peer-reviewed scientific journals following the program, averaging over 5 publications per participant. These publications have been cited over 4000 times with an average of over 13 citations per paper. Large proportion of program participants have continued contributing to health research; the vast majority of program participation chose to continue at the University of Michigan. Survey results indicate participants’ belief that the program had wide-ranging and enduring impacts on key aspects of their careers, including their application of research to practice. Interviews confirmed that the program helped many participants make substantial advancement in their careers. DISCUSSION/SIGNIFICANCE: Training programs for health research staff and clinicians can have a substantial and enduring impact on their professional development and advancement. The need for programs like PORT will increase as the health research workforce grows. These results inform recommendations for translational scientists.